2018
DOI: 10.1039/c8ew00056e
|View full text |Cite
|
Sign up to set email alerts
|

Metaldehyde removal from drinking water by adsorption onto filtration media: mechanisms and optimisation

Abstract: a Trace micropollutants should be removed during drinking water production without increasing the disinfection-by-product formation potential or energy demand of the treatment process. We demonstrate the efficacy of different filtration media to remove metaldehyde through controlled batch experiments on water augmented with metaldehyde. Equilibrium concentrations of metaldehyde and surrogate organics were successfully described by the Freundlich isotherm. Metaldehyde can be attenuated to varying degrees with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…11,12 Recently, there has been a study of metaldehyde adsorption with the presence of serine, leucine, and resorcinol onto different filtration media including different sands, GAC, and biological activated carbon (BAC); results have shown that BAC is very effective for metaldehyde removal. 13 This suggests that BAC filtration might be a feasible option for water treatment plants. However, there was observed desorption of metaldehyde from BAC back into the water, indicating that increased regeneration of BAC is required to maintain the effectiveness of metaldehyde removal which limits its economical application.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…11,12 Recently, there has been a study of metaldehyde adsorption with the presence of serine, leucine, and resorcinol onto different filtration media including different sands, GAC, and biological activated carbon (BAC); results have shown that BAC is very effective for metaldehyde removal. 13 This suggests that BAC filtration might be a feasible option for water treatment plants. However, there was observed desorption of metaldehyde from BAC back into the water, indicating that increased regeneration of BAC is required to maintain the effectiveness of metaldehyde removal which limits its economical application.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was observed desorption of metaldehyde from BAC back into the water, indicating that increased regeneration of BAC is required to maintain the effectiveness of metaldehyde removal which limits its economical application. 13 Our previous research has shown that PAC, an alternative adsorbent to GAC, can remove metaldehyde very efficiently even in the presence of natural organic matter (NOM). 14 In fact, it was reported that PAC has a much higher adsorption capacity (28 mg g −1 ) for metaldehyde 14 13 Busquets et al explained that the adsorption of metaldehyde is affected by the pore size distribution of the carbon materials and a higher adsorption capacity was observed in microporous carbon materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations